Assessment of Changes in Soil Infiltration, Water-Holding Capacity, Bulk Density and Fertility Parameters under Different Tree- and Crop-Based Systems in Semiarid Alfisols. Issue 5 (9th March 2017) - Ramulu, I.; Ramachandrappa, B. K.; Maruthi Sankar, G. R.; Sathish, A.; Sandhya Kanthi, M.; Archana, A. M.
ABSTRACT: Field experiments were conducted to assess changes in soil infiltration, water-holding capacity (WHC), bulk density and soil fertility with 15 custard apple (CA)-based systems of T1:CA+Fingermillet; T2:CA+Fodder Maize; T3:CA+Fieldbean; T4:CA+Niger; T5:CA+Chilli; T6:CA+Cowpea; T7:CA+Foxtailmillet; T8:Fingermillet; T9:Fodder Maize; T10:Fieldbean; T11:Niger; T12:Chilli; T13:Cowpea; T14:Foxtailmillet and T15:CA in 2012 and 2013 under semiarid Alfisols at Bangalore. T2 gave the maximum CA equivalent yield (1333 kgha −1 ), rainwater-use efficiency (4.90 kgha −1 mm −1 ), net returns of Rs. 52690 ha −1 and a benefit-cost ratio of 2.92. T6 gave the maximum WHC of 41.0%; an infiltration rate of 33.1 cmhr −1 ; a cumulative infiltration of 66.2 cm; and a minimum bulk density of 1.40 gcc −1 . T6 maintained maximum soil nitrogen (N) of 259 kgha −1 ; phosphorus pentoxide (P2 O5 ) of 67.9 kgha −1 ; and potassium oxide (K2 O) of 141.5 kgha −1 ; while T9 gave uptake N of 102.7 kgha −1 ; P2 O5 of 24.6 kgha −1 ; and K2 O of 103.7 kgha −1 . T6 was efficient for improving the soil physical, chemical, and biological parameters based on the study.